Efek pemberian ekstrak etanol daun sintrong (Crassocephalum crepidioidies) terhadap penurunan berat badan tikus jantan - Muharni Saputri; Salmah Handayani Lubis; Fenny Hasanah; Siti Muliani Julianty; Muflihah Fujiko; Ernawaty Ginting; Anggi Salsabilah Nasution; Kiki Mariana Batubara (Journal of Pharmaceutical and Sciences, 2023)
One of the medicinal plants that has the effect of reducing obesity is the sintrong plant. This plant has tannins, saponins, polyphenols, and flavonoids so that it can reduce blood glucose levels as an antidiabetic effect and can reduce weight. The purpose of this study was to see the occurrence of weight loss in test animals by administering ethanol extract of sintrong leaves and to find out whether the different doses of sintrong leaves can reduce body weight in male white rats. The research method was carried out experimentally, then testing the effectiveness of the ethanol extract of sintrong leaves using 25 rats which were divided into groups I to V with varying doses of 250 mg, 500 mg, and 750 mg, and carried out statistically by the Tukey method. The results of this acquisition when compared with the comparison group are not much different. Based on the result obtained, group V was given a suspension of ethanol extract of sintrong leaves at a dose of 750 mg/kgBW and the comparison group was given orlistat haven’t significant difference based on a statistical test with α > 0.05 so it could be concluded that there was a decrease in body weight in rats after administration of ethanol extract of sintrong leaves at a dose of 750mg/kgBW.